Legal Perspectives of Serbia’s Healthcare Digitalization. COVID-19 as a Catalyst for Change - Nikolić Popadić, Sofija; Stanojević, Petra (Review of European and Comparative Law, 2026)
The COVID-19 pandemic highlighted the critical need for the digitalization of healthcare services worldwide, acting as a catalyst for innovation and prompting governments to reassess healthcare infrastructure and implement legislative and organizational frameworks to support the broader adoption of eHealth solutions. This paper examines Serbia’s response during and after the pandemic, addressing whether the experience led to tangible changes in healthcare digitalization. It investigates whether these changes remain largely confined to policy documents and legislation, or if they have been effectively implemented in practice. furthermore, the study identifies areas where additional improvements are required to ensure that digital healthcare can reach its full potential. Understanding these developments is crucial, not only for preparing for future pandemics but also for responding to other emergencies, improving access to healthcare in remote areas, and supporting vulnerable populations, including older adults. By analyzing Serbia’s experience, this paper aims to provide insights into how crises can accelerate digital transformation in healthcare systems and to inform strategies for creating resilient, efficient, and equitable health infrastructures.